Lesion Sterilization and Tissue Repair: A Comprehensive Review - Dr. Hussain Topiwala; Dr. Sumit Bhatt; Dr. Alcina Fernandes; Dr. K.V. Phani Teja Gupta; Dr. Sonali Harish; Dr. P. Arulraj (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Lesion Sterilization and Tissue Repair (LSTR) is an innovative therapeutic approach designed to manage deep dental caries and necrotic pulp, particularly in pediatric patients. This review explores the fundamental principles, clinical applications, and effectiveness of LSTR in preserving natural tooth structure while promoting tissue regeneration. The technique involves the application of a combination of antimicrobial agents, such as metronidazole, ciprofloxacin, and minocycline, to eliminate pathogenic bacteria and create an optimal environment for healing. The review highlights the indications and contraindications of LSTR, as well as factors affecting its success. Collectively, the findings suggest that LSTR can significantly improve treatment outcomes in pediatric dentistry, providing a less invasive alternative to traditional methods. Ongoing research and clinical trials are essential for refining LSTR protocols and establishing its long-term efficacy and safety.